UNA VIDA EN LOS DÍAS DE LOS SUI-TANG - Calderón Méndez, José Rafael (2012)
“A Life in the Days of Sui-Tang” it is a story that revolves around a character called Yinyüé, who works in different situations of Medieval China of the Sui and Tang dynasty, and presents several facets throughout his life. This narrative pretends to show the lifestyle of the different inhabitants who lived on Medieval China. It also seeks to expose through fictitious situations based on historical facts: suffering, impotence, discomfort, and desires; and other human feelings experienced by the lowest classes of society of ancient Medieval China; as well as the search for inner peace and spiritual balance of the individual in a society in which everyday life was determined by the willing of the empire.